DIFFERENCES OF VASCULAR ENDOTHELIAL GROWTH FACTOR (VEGF) EXPRESSION IN VARIOUS MENINGIOMA EDEMA INDEX - agrina, puspa (Universitas Hang Tuah, 2024)
Background: Meningiomas are the most common primary intracranial tumor in adults after glioma. Vascular endothelial growth factor (VEGF) is a key protein in the formation of new blood vessels (angiogenesis). In meningiomas, binding of VEGF to the VEGF receptor (VEGFR) through activation of the Ras/MAPK signaling pathway and control of vascular permeability through the PLCγ pathway peritumoral (PTBE). Sixty percent of meningiomas are associated with peritumoral brain edema (PTBE). Objective: This study aims to determine differences in VEGF expression on various indices of meningioma edema. Methods: An analytical observational study with consecutive sampling in 69 samples diagnosed with meningioma with MRI data. VEGF expression variables based on Immunohistochemistry were classified into scores of 0, 1+ and 2+. Variable PTBE Meningiomas assessed by the edema index based on MRI were classified into grades 1,2 and 3. Results: Based on Spearman's correlation test, there was no significant difference between VEGF expression on various meningioma edema indices (p = 0.333). Conclusion: There was no significant difference between VEGF expression on various meningioma edema indices (p = 0.333).